ORGANIZATIONAL CITIZENSHIP BEHAVIOR: PERAN PERSON JOB-FIT, MOTIVASI INTRINSIK, PERCEIVED SUPERVISOR SUPPORT PADA KANTOR SATUAN POLISI PAMONG PRAJA DIY - Pambudi, Isnain Rio; IKurniawan, Ignatius Soni (Jurnal Manajemen Terapan dan Keuangan, 2024)
This riset intends to examine the influence of person job-fit, intrinsic motivation, perceived supervisor support on OCB. The riset used a population of all employees of the Yogyakarta Civil Service Police Unit (Satpol PP). Data were collected by questionnaire from 41 employees and using multiple linear regression analysis method and classical assumption test. The classical assumption test includes muticolonierity test, normality test and heteroscedasticity test. The results of this study indicate that person job-fit has a significant positive effect on OCB, intrinsic motivation has no significant effect on OCB, perceived supervisor support has a significant positive effect on OCB. The relevance of the study results will be discussed in the discussion.